England on the eve of the industrial revolution : a study of economic and social conditions from 1740 to 1760 with special reference to Lancashire /: a study of economic and social conditions from 1740 to 1760 with special reference to Lancashire. ([2013?]) - Moffit, Louis W (Louis Wilfrid), 1887
No abstract available